Coastal and inland water monitoring using a portable hyperspectral laser fluorometer. Issue 1 (15th June 2017) - Chen, Peng; Pan, Delu; Wang, Tianyu; Mao, Zhihua; Zhang, Yiwei
Abstract: The potential for a ship-mounted laser fluorometer to provide rapid, non-intrusively measurements in both coastal and lake conditions are investigated. The instrument consists of a high pulse repetition frequency (10-kHz) microchip laser for fluorescence excitation, a broadband hyperspectral micro spectrometer for spectral detection, and a confocal reflective fluorescent probe for signal collection; it weighs only about 1.7 kg. Chlorophyll a (chl- a ) and colored dissolved organic matter (CDOM) measured by the new instrument were observed to agree well with those measured by traditional time-consuming laboratory methods in Hangzhou Bay seawater and Qiandao Lake inland water. Subsequently, laser fluorescence distribution and characteristics of chl- a and CDOM in these regions were analyzed, which will improve our understanding of biogeochemical processes in these optically complex aquatic systems. The portable system is promising for water environment monitoring, especially in coastal and inland water. Highlights: A laser fluorometer for coastal and inland water monitoring was developed. A high pulse repetition frequency laser was used to improve SNR. Laser fluorescence distribution and characteristic in these regions were analyzed. Conservative mixing and nutrients exchange were found in Hangzhou Bay.